The privilege of being banal: art, secularism, and Catholicism in Paris - Oliphant, Elayne (Class 200, 2020)
Introduction: The Privilege of Banality -- Part One: Curating Catholic Privilege -- Evangelization and Normalization -- Crystallization and Renaissance -- Part Two: Mediating Catholic Privilege -- Walls That Bleed -- Learning How to Look -- Part Three: Reproducing Catholic Privilege -- The Immediate, the Material, and the Fetish -- The Banality of Privilege